2007
DOI: 10.1002/anie.200700455
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Helical Structure of the Stereocomplex Composed of Complementary Isotactic and Syndiotactic Poly(methyl methacrylate)s as Revealed by Atomic Force Microscopy

Abstract: The DNA double helix composed of complementary strands is of fundamental importance for the exquisite functions of DNA, such as the replication and storage of genetic information. Since the discovery of the DNA double helix, [1] the design and synthesis of artificial double helices have attracted significant attention but remain a great challenge in polymer and supramolecular chemistry.[2] In particular, double helices of complementary strands are quite rare. [3] The complex formed from complementary strands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 35 publications
12
161
0
Order By: Relevance
“…92 The AFM image of the stereocomplex (Figure 13c) prepared from a mixed monolayer of it-and st-PMMA chains spread on a water surface upon compression showed helix- Synthesis and structures of helical polymers E Yashima bundle-like structures, which can be further resolved into individual stripe-patterned chains with a chain-chain lateral spacing of B2.4 nm. 93 In the high-resolution zoomed image (Figure 13d), a number of periodic oblique stripes (green arrows) with a pitch of 0.92 nm can be observed, which are tilted either clockwise or counterclockwise along the stereocomplex main chain (pink lines) (Figure 13d). These results clearly indicate that the stereocomplex is certainly a supramolecular multistranded helical polymer.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…92 The AFM image of the stereocomplex (Figure 13c) prepared from a mixed monolayer of it-and st-PMMA chains spread on a water surface upon compression showed helix- Synthesis and structures of helical polymers E Yashima bundle-like structures, which can be further resolved into individual stripe-patterned chains with a chain-chain lateral spacing of B2.4 nm. 93 In the high-resolution zoomed image (Figure 13d), a number of periodic oblique stripes (green arrows) with a pitch of 0.92 nm can be observed, which are tilted either clockwise or counterclockwise along the stereocomplex main chain (pink lines) (Figure 13d). These results clearly indicate that the stereocomplex is certainly a supramolecular multistranded helical polymer.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…The authors subsequently proposed a triplestranded helix model to explain the poly(methyl methacrylate stereocomplex; their model was supported by direct evidence from AFM phase images. 49 Cheuk et al 50 have reported similar results, in which amphiphilic chains of a chiral polymer self-assembled into a variety of organizational morphologies, including twisting cables, spiral ribbons, spherical vesicles and helical nanotubes. Moreover, Goh et al 51 investigated the relationship between the concentration of a chiral dopant and the helical pitches of a nematic LC induced by the dopant.…”
Section: Chiral Interaction-induced Morphological Changes In Smart Pomentioning
confidence: 80%
“…AFM has been shown to be an effective tool in identifying and visualizing polymer helices. 2c, 19 In the case of helical polyisocyanides, 20 polyacetylenes 21 and polymethacrylates, 22 helical shapes of chains have been clearly observed. Fig.…”
Section: Chart 1 Structure Of Poly(bmbpst)mentioning
confidence: 97%